2017
DOI: 10.1088/1361-648x/aaa18a
|View full text |Cite
|
Sign up to set email alerts
|

Spin dynamics of FeGa3−xGexstudied by electron spin resonance

Abstract: The intermetallic semiconductor FeGa<sub>3</sub> acquires itinerant ferromagnetism upon electron doping by a partial replacement of Ga with Ge. We studied the electron spin resonance (ESR) of high-quality single crystals of FeGa<sub>3-x</sub>Ge<sub>x</sub> for x from 0 up to 0.162 where ferromagnetic order is observed. For x = 0 we observed a well-defined ESR signal, indicating the presence of pre-formed magnetic moments in the semiconducting phase. Upon Ge doping the occurr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Based on the crystal growth results presented here, first measurements of physical properties of binary FeGa 3 and FeGa 3− x Ge x have already been published without mentioning details of the single crystal growth approach . It is outside the scope of the present paper to repeat the results of the physical studies here.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Based on the crystal growth results presented here, first measurements of physical properties of binary FeGa 3 and FeGa 3− x Ge x have already been published without mentioning details of the single crystal growth approach . It is outside the scope of the present paper to repeat the results of the physical studies here.…”
Section: Discussionmentioning
confidence: 94%
“…Starting from a semiconductor, with increased Ge doping the compound performs a crossover to a strongly correlated metal at x = 0.06. [11,18] Arising from the sensitivity of strongly correlated materials to chemical doping, it was found that at the critical Ge concentration of around x = 0.15, the phase shows quantum critical fluctuations and a phase transition from antiferromagnetic to itinerant ferromagnetism at low temperatures. While antiferromagnetic quantum critical systems have already been studied in 4f-and 3d-systems, ferromagnetic quantum criticality is of significant interest for basic research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dotted lines for FeAs2 and FeGa3 are activation-law fit extrapolations. CrSb2 is antiferromagnetic below 273K; a complex magnetic order has also been suggested for FeGa3 [36,94].…”
Section: A Correlated Narrow-gap Semiconductors: a Brief Overviewmentioning
confidence: 89%
“…• FeSi 1−x Ge x : ferromagnetic metal above x = 3 The onset of a peculiar antiferromagnetic order in CrSb 2 below 273K [65,95] has no visible signature in the susceptibility. 4 with the exception of CrSb 2 below its Néel temperature T N = 273K, and possibly FeGa 3 [36,94].…”
Section: A Correlated Narrow-gap Semiconductors: a Brief Overviewmentioning
confidence: 99%